Pengaruh Informasi Lingkungan dan Sosial terhadap Keputusan Manajer (Studi Eksperimen di PT Hanjaya Mandala Sampoerna, Tbk) - Wulan Dari (Master in Accounting Program, 2014)
Currently, social and environmental issues emerge in business and accounting literature. Previous accounting studies, however, only focused on how external parties (investors) used this information. Different with majority of previous studies, the currently study examines whether managers, as internal users, consider social and environmental information in their project evaluation decision. The study is experimental study from managers in PT Hanjaya Mandala Sampoerna, Tbk, affiliate company of Philips Morris International in Indonesia. Built on the stakeholder theory, this study hypothesis’s that managers as internal party consider social and environmental information.